2014
DOI: 10.1088/0031-8949/89/11/115809
|View full text |Cite
|
Sign up to set email alerts
|

Theory of s-wave superconductor containing impurities with retarded interaction with quasiparticles

Abstract: We propose a perturbation theory and diagram technique for a disordered metal when scattering of quasiparticles by nonmagnetic impurities is caused with a retarded interaction. The perturbation theory generalizes a case of elastic scattering in a disordered metal. Eliashberg equations for s-wave superconductivity are generalized for such a disordered superconductor. Andersonʼs theorem is found to be violated in the sense that embedding of the impurities into an s-wave superconductor increases its critical temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Contrary to this, the presence of defects and thermal vibrations in the film contributes to scattering. However, previous studies have indicated that the interaction of quasiparticles with nonmagnetic impurities can be retarded in disordered s-wave superconductors [37,38]. For a strongly disordered system, the electrons are blocked between impurities.…”
Section: Resultsmentioning
confidence: 98%
“…Contrary to this, the presence of defects and thermal vibrations in the film contributes to scattering. However, previous studies have indicated that the interaction of quasiparticles with nonmagnetic impurities can be retarded in disordered s-wave superconductors [37,38]. For a strongly disordered system, the electrons are blocked between impurities.…”
Section: Resultsmentioning
confidence: 98%
“…The tunneling of the pairs by the negative pair-hopping interaction J ef f in our effective model known as the Suhl-Kondo mechanism is responsible for the enhancement of superconductivity due to the inter-band scattering [42][43][44]. In ADF's, the phonons are localized on own C 60 molecular sites and they do not propagate to neighboring molecules as much as phonon propagation in usual metal [30]. Even though, the momentum is well defined in the crystal, the phonons are Holstein phonons and their dispersion is flat.…”
Section: The Effective Modelmentioning
confidence: 99%
“…The intra-molecular Jahn-Teller phonon coupling constants are given by λ ν . Here V ν mm ′ are the elements of coupling matrices V ν , which is determined by icosahedral symmetry [30,31].…”
Section: The Effective Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However these facts does not change the previous conclusions. In [7][8][9] a method to consider electron-phonon interaction has been proposed, however the resulting equation is much simpler than Eliashberg equations. Phonons are dispersionless ω(q) = ω and the electron-phonon coupling constant does not depend on a wave vector λ(q) = λ are suggested in this method.…”
Section: Introductionmentioning
confidence: 99%